2014
DOI: 10.1088/0004-637x/794/2/167
|View full text |Cite
|
Sign up to set email alerts
|

Binaries Traveling Through a Gaseous Medium: Dynamical Drag Forces and Internal Torques

Abstract: Using time-dependent linear theory, we investigate the morphology of the gravitational wake induced by a binary, whose center of mass moves at velocity V cm against a uniform background of gas. For simplicity, we assume that the binary's components are on circular orbits about their common center of mass. The consequences of dynamical friction is twofold. First, gas dynamical friction may drag the binary's center of mass and cause the binary to migrate. Second, drag forces also induce a braking torque, which c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…In addition, it has been argued that dynamical friction due to the gas generates torques which tend to harden the binary [61]. This will add up to the effect we put forward here.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, it has been argued that dynamical friction due to the gas generates torques which tend to harden the binary [61]. This will add up to the effect we put forward here.…”
Section: Discussionmentioning
confidence: 58%
“…Only a few values of R φ are given, but Kim et al (2008) showed that R φ is a function of M orb . Without an understanding of how R φ scales with M orb , we are unable to include results from Sánchez-Salcedo & Chametla (2014) in Figure 13, although such a comparison is highly desirable.…”
Section: Comparison To Previous Workmentioning
confidence: 99%
“…We do not account for the companion's wake in our simulation. By doing that, we overestimate GDF force by at most 2 − 3 times, according to both Kim et al (2008) and Sánchez-Salcedo & Chametla (2014). Moreover, for typical planetesimal masses and for eccentric primary orbit, v out v bin .…”
Section: And Applicabilitymentioning
confidence: 86%
“…If the outer binary moves with relative velocity v out with respect to the gas, the morphology of the wake is different. Sánchez-Salcedo & Chametla (2014) have shown that the braking torque that causes the binary to lose angular momentum, is Γ = αa bin F (1)…”
Section: And Applicabilitymentioning
confidence: 99%